Evaluation of the effectiveness of painting therapy on health anxiety, loneliness and death anxiety in the elderly - Asadi , Leyla; Seirafi , Mohammadreza; Ahadi, Morvarid (Applied Family Therapy Journal (AFTJ), 2023)
Aim: The aim of this study was to determine the effectiveness of painting therapy on health anxiety, loneliness and death anxiety in the elderly. Methods: The research method was quasi-experimental with pre-test-post-test design with experimental group and control group with a follow-up test period. From the statistical population of the elderly living in nursing homes in Tehran in 2021, 30 samples were selected by convenience sampling and randomly divided into two experimental groups and a control group. Painting therapy was applied for ten sessions for the experimental group. The required findings were collected using the Health Anxiety Questionnaire (Salkovskis & Warwick, 2002), Loneliness (Dehshiri et al., 2007) and Templer Death Anxiety (1970) and were analyzed using repeated measures analysis of variance was analyzed. Results: Findings showed that the mean scores of post-tests and follow-up test of health anxiety, loneliness and death anxiety in the experimental group decreased and the results of repeated measures analysis of variance showed that painting therapy intervention to reduce health anxiety, loneliness and death anxiety in the elderly is effective (p <0.001). Conclusion: Therefore, it is suggested that painting therapy intervention be used to reduce health anxiety, loneliness and death anxiety in the elderly.